Long-term continuous mono-cropping of Macadamia integrifolia greatly affects soil physicochemical properties, rhizospheric bacterial diversity, and metabolite contents - Tao, Liang; Zhang, Chunsheng; Ying, Zhiping; Xiong, Zhi; Vaisman, Haim Shalom; Wang, Changming; Shi, Zhuogong; Shi, Rui (Frontiers in Microbiology, 2022)
Macadamia integrifolia is the most economically important Proteaceae crop known for its edible nuts. The present study was conducted to examine the effect of continuous monoculture cultivation of M. integrifolia on soil quality, bacterial diversity, and metabolites in three different Macadamia rhizosphere orchards: 1-year monoculture orchard = CK; 5-year monoculture orchard = Y5; and 20-year monoculture orchard = Y20, through metagenomic and metabolomic profiling. The soil physicochemical properties including organic matter, and available nutrients (P, N, and K) were first increased significantly (p<0.05) in from CK to Y5 group and then decreased (p<0.05) from Y5 to Y20 group. The soil pH continuously decreased (p<0.05) over time from CK to Y20. Metagenomic profiling revealed that Actinobacteria, Acidobacteria, and Proteobacteria were the top three abundant phyla with their inconsistent relative abundance patterns from CK to Y20 (CK: 23.76%, Y5: 34. 06%, and Y20: 31.55%), (CK: 13.59%, Y5: 18.59%, and Y20: 21.35%), and (CK: 27.59%, Y5: 15.98%, and Y20: 17.08%), respectively. Overall bacterial diversity first increased and later decreased in the continuous monoculture orchards. KEGG annotation analysis revealed cellular processes, organism systems, metabolism, and genetic information were the most enriched functional categories. CAZy database screening indicated the highest enrichment of glycoside hydrolases following the glycoside transferases and carbohydrate-binding modules. Differential metabolite analysis revealed the highest number of metabolites (11) in the Y5 group than in Y20 group (6). It is concluded that continuous monoculture of M. integrifolia improves the soil physicochemical properties, bacterial diversity, and metabolites profiles in short-term planted orchards which is however deteriorated in long-term planted orchards.